2021
DOI: 10.4049/immunohorizons.2100070
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity Increases Susceptibility to and Mortality from Sepsis

Abstract: We recently demonstrated how sepsis influences the subsequent development of experimental autoimmune encephalomyelitis (EAE) presented a conceptual advance in understanding the postsepsis chronic immunoparalysis state. However, the reverse scenario (autoimmunity prior to sepsis) defines a high-risk patient population whose susceptibility to sepsis remains poorly defined. In this study, we present a retrospective analysis of University of Iowa Hospital and Clinics patients demonstrating increased sepsis prevale… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…[6, 7, 11] However, recent studies have yielded divergent and even contradictory ndings across different types of AID. [5,6,8,12,25] Not to mention con rming the causal relationship between AID and sepsis, which could have been achieved through MR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[6, 7, 11] However, recent studies have yielded divergent and even contradictory ndings across different types of AID. [5,6,8,12,25] Not to mention con rming the causal relationship between AID and sepsis, which could have been achieved through MR.…”
Section: Discussionmentioning
confidence: 99%
“…MS is a central nervous system disorder involving autoimmune demyelination, which is mediated by various in ammatory cells. [5,39] The association between sepsis and MS is intricate. On one hand, sepsis has been postulated to signi cantly contribute to the development of MS, as demonstrated by a recent retrospective cohort study conducted in Taiwan, which reported a nearly threefold increased likelihood of MS development among patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, heightened basal inflammation is not only observed after sequential infection (or acute infections) but also during autoimmune settings, such as experimental autoimmune encephalomyelitis (EAE; murine model of multiple sclerosis). Importantly, Jensen et al (53) show that EAE mice have increased mortality to CLP when EAE-induced inflammation is elevated; however, the cell type contributing to the elevated steady-state inflammation was not interrogated.…”
Section: Discussionmentioning
confidence: 99%